The Modern Trends of Financial Reporting Development - Olga V. Rozhnova (Учёт. Анализ. Аудит, 2019)
Introduction, Purpose. The trends in the development of financial reporting are influenced by many factors, including such as the information preferences of the stakeholders, the state of the economy, the level of development of information technologies, etc. Considerable changes are observed in almost all the above mentioned factors, during the twenty-first century, there was a spark in the emergence of new trends in the development of financial statements, or some modification of the trends that existed previously. In this regard, to continue work on conceptual, methodological, and practical issues relating to the financial statements, it is necessary to have a scientific understanding and analysis of current trends in its development. Such a study is logically to be primarily conducted on the IFRS-based reporting which Russian Accounting Standards focuses on. The purpose of the article was to identify the modern trends in the development of financial reporting (IFRS-reporting). Tasks included: the review of scientific research trends in this field; the comparison of trends in financial reporting and financial accounting; the identification of public and private trends in financial reporting. The study was conducted for the traditional scientific conference in the memory of Sarah Bentsionovna Barngoltz “the Standardization of accounting and control and analytical processes” organized by the Department of accounting, analysis and auditing of the Financial University under the Government of the Russian Federation in 2017. Methods. The article uses the following methods of scientific research - analysis, synthesis, induction, deduction, systems approach, comparison, generalization. Results. The main conclusions of the article are as follows: on the basis of the analysis of the vector of changes in IFRS and opinions on the research questions of scholars and practitioners, there were highlighted the General trends for the accounting sphere such as standardization that was caused by globalization which is strengthening it even further; and the increasing interaction between different areas of the accounting sector (its expansion); it was proposed to update the General trends by adding another trend to the existing - the customization of information of the financial reporting; there were selected the individual development trends - the focus on the forecast; the emphasis on the information that reveals the warning actions of the company, the extension of the application scope of the method of professional judgment, communicating professional judgments to the users of financial statements; strengthening of the prevalence principle of economic entity over its legal form; the focus of the rules on the purposeful use of accounting information, the integration of financial reporting with non-financial reporting. Discussion. The results obtained do not fundamentally contradict the findings of other scientists, but to complement these findings, and in some cases refocus them. In the future the study of trends in the development of financial reporting should be continued, due to the constant progressive movement of both - the economy, user requirements, the requirements for accounting information, the digital transformation in distribution and processing of information and the theory of accounting. The complexity of the way to it is natural, as the identification of the trends, their interpretation and description is a continuous process, aimed not only at summarizing of the next stage of development of the financial statements, but also on the creation of a prototype of the future stage.